Pengacakan Posisi Plaintext Menggunakan Kunci Blok Persegi pada Proses Enkripsi dengan Algoritma Arnold’s Cat Map - Andysah Putera Utama Siahaan; Melva Sari Panjaitan (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Plaintext is a message or information in the original form that has a text format. Plaintext can be opened using any text editor application because the plaintext information preparation system does not use a security key. In securing the message, the plaintext must be given a series of commands or program code to turn the plaintext into an encrypted message. The technique used in this study uses a transposition scheme, namely by rearranging the location of the characters without replacing the plaintext characters with other characters. The level of difficulty in this process depends on the parameter values ??B and C given and the iteration value used to generate the ciphertext. This study uses character arrangement with a 4 x 4 matrix pattern where each plaintext block will be divided based on 16 characters. Each block will be encrypted using a map that has been generated by Arnold's Cat Map. The results of the study found that the plaintext could be scrambled properly during the encryption process and was successfully returned to the original message at the time of decryption.